2002
DOI: 10.3354/meps229001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal effluents from a power station on bacteria and heterotrophic nanoflagellates in coastal waters

Abstract: To investigate effects of thermal effluents from a coastal power station on bacteria and heterotrophic nanoflagellates (HNF) in adjacent coastal waters, surface distributions of bacteria and HNF and interrelations between microbial and environmental variables were studied in November 1998 and July, August and November 1999 near Hadong Power Station, Korea. In addition, manipulation experiments with treatments of high temperature (40°C; temperature in the cooling system of the power station) and additions of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…Sea surface temperatures in the Bay of Blanes (NW Mediterranean) can vary by ~10°C over the usual annual seasonal cycle (Alonso-Sáez et al 2008), and additional sources of variability may change the sea surface temperature of coastal ecosystems by several degrees Celsius in shorter periods of time, such as during extreme heat waves or in the vicinity of the thermal effluents of power stations (Choi et al 2002). In addition, global sea surface temperatures have been increasing at rates near 0.01°C yr −1 since the 1860s (Levitus et al 2000, Vargas-Yañez et al 2005, Mackenzie & Schiedek 2007, and some climatic models predict an increase in atmospheric temperatures ranging between 2.5 and 5°C in the Mediterranean region by the end of the century (Christensen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sea surface temperatures in the Bay of Blanes (NW Mediterranean) can vary by ~10°C over the usual annual seasonal cycle (Alonso-Sáez et al 2008), and additional sources of variability may change the sea surface temperature of coastal ecosystems by several degrees Celsius in shorter periods of time, such as during extreme heat waves or in the vicinity of the thermal effluents of power stations (Choi et al 2002). In addition, global sea surface temperatures have been increasing at rates near 0.01°C yr −1 since the 1860s (Levitus et al 2000, Vargas-Yañez et al 2005, Mackenzie & Schiedek 2007, and some climatic models predict an increase in atmospheric temperatures ranging between 2.5 and 5°C in the Mediterranean region by the end of the century (Christensen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These HNF abundances were within the range of those in anoxic hypolimnia of stratified lakes (Bloem et al 1989, Hadas & Berman 1998, Kopylov et al 2002, Saccà et al 2008. Previous studies demonstrated that abiotic factors regulate HNF abundance (McManus & Fuhr man 1990, Choi et al 2002. Therefore, our data using Spearman's rank correlation analysis suggest salinity and temperature are the factors that affect HNF abundance in the oxic and suboxic layers, respectively, whereas no significant correlation was found between the abundances of HNF and bacteria (Table 1).…”
Section: Discussionmentioning
confidence: 78%
“…Servias & Billen (1989) showed that bacteria could tolerate higher temperatures than phytoplankton near the Muse power plant. Near the Hadong power station (Korea), Choi et al (2002) demonstrated that a temperature of 40°C inhibited BP by 23 to 69%, but had no effect on heterotrophic nanoflagellates. This indicated that larger heterotrophs might endure a higher magnitude of thermal stress than phytoplankton and bacteria.…”
Section: The Outlet and The Plume Systemsmentioning
confidence: 99%
“…Related studies of thermal stress on planktonic activities have been conducted elsewhere, but with limited measurements. For example, Servais & Billen (1989) studied the thermal effects on primary and bacterial production, and Choi et al (2002) worked on the influence of thermal stress on the activity of heterotrophic bacterioplankton and nanoflagellates. The system characteristic CR was not analyzed in either study.…”
Section: Introductionmentioning
confidence: 99%